Finite element analysis of dental aligners - Tan, Daniel Jing Quan (2019)
In recent years, it is increasingly common to see more people undergoing orthodontic treatments for aesthetic reasons. Clear dental aligners, in particular, are a suitable and preferred choice for both adults and teenagers as they are almost invisible and can be removed freely. For patients with very mild cases of misaligned teeth, it may not be practical to undergo orthodontic treatment. Hence, the author is looking at the possibility of designing and making dental aligners for patients with very mild cases of misaligned teeth. In this project, the author aimed to establish a set of systematic steps for the design and generation of a series of aligners for orthodontic correction of mild cases. Finite Element Analysis of the designed dental aligners is then performed using ANSYS Mechanical to measure the pressure distribution on the aligners. This report describes the set of steps established by the author which includes dealing with a 3D dental model in STL file format, 3D modelling of a dental model using ANSYS SpaceClaim and the modelling of the ‘dental model and aligner’ contact pair in ANSYS Mechanical for performing finite element analysis. This report also showed some of the results of the finite element analysis and discussed the effectiveness and limitations of the methodology.